Building Up Students’ Speaking Achivement Through Jigsaw Technique - Helmi Syukur (Jurnal Adabiyah: Humanities and Islamic Studies, 2016)
This research aimed to describe about whether or not the use of jigsaw technique significantly builds up the speaking achievement of participants of PIBA of UIN Alauddin Makassar and the use of jigsaw technique interesting to the participants of PIBA of UIN Alauddin Makassar. This research applied quasi experimental research and it employed purposive sampling technique. Two groups of the advance level of PIBA academic year 2012/ 2013 of UIN Alauddin Makassar. There are 30 participants from experimental group and 30 participants from control group. The data were collected using test and questionnaire. The data of students’ learning achievement on English speaking collected by using questionnaire. Those data were then analyzed descriptively and inferentially. The result of data analysis indicated that the jigsaw techniques built up significantly the students speaking achievement of advance levels after the treatment. Jigsaw technique effective in improving English speaking achievement of the students better than conventional activity as indicated by the T-Test value 24.403 and the P-Value (2 tailed). 000 which was not greater than 0.5 level of significance, and the students were interested in learning English speaking using Jigsaw technique which was indicated the mean score 85.97. It means that the students were classified very high interested students.